Der "jüdisch-christliche" Dialog veränderte die Theologie: ein Paradigmenwechsel aus ExpertInnensicht - Petschnigg, Edith; Fischer, Irmtraud (De Gruyter eBook-Paket Theologie, Religionswissenschaften, Judaistik, 2016)
Has "Jewish-Christian dialogue" changed theology? The essays collected in this volume lend clear evidence to a paradigm change in theology during the decades after the Second World War. The book also lends insight into the personal evolution of the researchers involved, thereby offering a slice of reflective theological history.